The Correlation Between Students’ Reading Motivation and Their Reading Comprehension in Narrative Text at Eighth Grade of SMP Negeri 1 Pekanbaru - Tia Novani Irawan; Wandi Syahfutra; Qona’ah Nuryan Arif (Lembaga Pengembangan Kinerja Dosen, 2025)
Students struggle to read English texts due to lack of motivation, difficulties in understanding complex language structures, and challenges with unfamiliar vocabulary, especially in narrative texts. This study aimed to investigate the correlation between students' reading motivation and their reading comprehension in narrative texts. This study used a correlational design. The sample consisted of 63 students of eighth grade students at SMP Negeri 1 Pekanbaru, selected using a simple random sampling technique. To collect data, the researcher used a questionnaire to assess students' reading motivation and an objective test to evaluate their reading comprehension in narrative texts. A Pearson correlation analysis showed a correlation coefficient (rxy) of 0.514, indicating a moderate positive relationship between the two variables. With a significance value of 0.000, which is less than 0.05, this correlation was found to be statistically significant. Furthermore, because the r-value (0.514) is greater than the r-table value (0.252) for 63 students at the 5% significance level, the alternative hypothesis (H1) is accepted and the null hypothesis (H0) is rejected. These results indicate that increased students' reading motivation is related to improved reading comprehension in narrative texts.